A Novel HDAC6 Inhibitor Ameliorates Imiquimod-Induced Psoriasis-Like Inflammation in Mice - Anqi Cao; Yurong Li; Yanqiao Feng; Xiaoquan Wang; Wenyu Wei; Hongyan Sun; Junmin Quan (Molecules)
Psoriasis is a chronic inflammatory skin disease characterized by abnormal proliferation of keratinocytes and infiltration of inflammatory cells. Significant challenges remain in developing effective and safe targeted therapies for psoriasis. Here, we reported the discovery of novel cystamine derivatives for the treatment of psoriasis. These compounds effectively attenuated LPS-induced inflammation in vitro, and the optimal candidate CS1 ameliorated imiquimod-induced psoriasis-like inflammation in mice. Mechanistically, CS1 bound and inhibited the deacetylase HDAC6, subsequently inhibited the AKT, MAPK, and STAT3 pathways, attenuated the hyperproliferation and altered differentiation of keratinocytes and reduced the infiltration of immune cells. These findings suggest that HDAC6 may serve as a potential target for drug development in the treatment of psoriasis.